Notions of artist as the hero : a Nietzschean reading on the philosophical relationship of Otto Rank and Sigmund Freud - Moilanen, Lauri Anssi (2019)
The goal of this study is to explore the development of Otto Rank's (1884-1939) philosophy through his shifting conceptions of heroism. The focus is specifically on the notion of Artist as the Hero. The investigation is conducted by performing a comparative study of Rank's thought with that of his two great mentors: Friedrich Nietzsche (1844-1900) and Sigmund Freud (1856-1939). The study employs various key concepts of Nietzsche – such as Apollonian / Dionysian dichotomy – to illustrate similarities and differences between Rank and Freud. Nietzsche acts here as a basis for comparison. This study argues that the psychologies of Rank and Freud – and their gradual divergence – can be seen as two different and unique answers to the challenge of nihilism, as expressed by Nietzsche with his conception of the Death of God and the cultural criticism that entails. It proposes that the notion of Artistic Hero in the philosophies of Rank, Freud and Nietzsche can be seen as a key concept, as they attempt to answer this dilemma. The study shows how the development of Rank's thought progresses from strict adherence to Freud's ideas to a point where he re-unites again with his early philosophical hero, Nietzsche, the artistic heroism acting as a connecting metaphor. The study elucidates how Rank uses Nietzsche to break away from Freud, and Freud, on the other hand, tries to perform a 'heroic escape' from Nietzsche's influence. In their quest for authenticity and new values, these three thinkers essentially create heroic myths of their own. Although the psychology of Freud and the philosophy of Nietzsche are well-known in both public and academic spheres, the same cannot be said about Rank, whose ideas still remain unknown and obscure to most. In its own small way, this study aims to rectify this situation by exploring 'Rankian' ideas. There is an added dynamism that comes from juxtaposing Rank's thought with Nietzsche and Freud's.